Carvajal syndrome. A rare case. - Phiske, M.M.; Jerajani, H.R.; Indurkar, V.A.; Mahajan, A.U. (European Journal of Pediatric Dermatology, 2007)
We report a case of an 8-year-old male who presented with multiple striate and focal yellow to grey keratoderma on palms and soles and woolly hair on the entire scalp from the age of 1 year. The microscopic examination of the hair was normal. Mild cardiomegaly with straightening of left heart border was seen on chest X-ray. ECG showed evidence of pulmonary P. Left ventricular cardiomyopathy was detected on 2-D Echo. Histopathology from a palmar lesion was suggestive of keratoderma. The combination of features of woolly hair, palmoplantar keratoderma and left ventricular hypertrophy were suggestive of Carvajal syndrome, which is a familial cardiocutaneous syndrome consisting of woolly hair, palmoplantar keratoderma and heart disease.